THE INFLUENCE OF TOP MANAGEMENT TEAM (TMT) CHARACTERISTICS TOWARD INDONESIAN BANKS FINANCIAL PERFORMANCE DURING THE DIGITAL ERA (2014-2018) - Mojambo, Gabriel A.M; Tulung, Joy Elly; Saerang, Regina Trifena (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
Despite the abundant opportunities in the Indonesian bank industry, the digital era began to challenge banks to fully embrace the use of technology (information) to prolong competitive advantage. An organization becomes a reflection of its top managers. In facing such challenges, Top Management Team (TMT) members' initiative to overcome the current status quo, will be reflected in the company under their management. For this reason, an effective TMT structure is mandatory during the digital era to digitalize banking firms. This research investigates the relationship between top management team characteristics and Indonesian banks' financial performance during the digital era. For top management team characteristics, this research includes functional background, gender diversity, average age, level of education, IT Expertise, and experience in years. While to measure the performance of Indonesian banks' financial performance the paper includes return on asset (ROA), capital adequacy ratio (CAR), and non-performing loan (NPL). The results show that gender diversity has positive significant influences on NPL, average age have positive significant influences on ROA, CAR, NPL, and IT expertise have positive significant influences on CAR.Keywords: Bank, Top Management Team, Financial Performance